Бӧр вои ме...: бӧрйӧм гижӧдъяс / А. С. Пушкин - Пушкин Александр Сергеевич (Коми книжное издательство, 1999)
Экземпляры: КР (19990928) / Инвентарный номер: у50425 / Цена: 15.00 / Сис.шифр: Р1 / Авт.знак: П 91 / ГРНТИ: 17 / ББК: 84(2=411.2)-5